Warm-up with Weighted Bat and Adjustment of Upper Limb Muscle Activity in Bat Swinging under Movement Correction Conditions. Issue 1 (February 2014) - Ohta, Yoichi; Ishii, Yasumitsu; Ikudome, Sachi; Nakamoto, Hiroki
The effects of weighted bat warm-up on adjustment of upper limb muscle activity were investigated during baseball bat swinging under dynamic conditions that require a spatial and temporal adjustment of the swinging to hit a moving target. Seven male college baseball players participated in this study. Using a batting simulator, the task was to swing the standard bat coincident with the arrival timing and position of a moving target after three warm-up swings using a standard or weighted bat. There was no significant effect of weighted bat warm-up on muscle activity before impact associated with temporal or spatial movement corrections. However, lower inhibition of the extensor carpi ulnaris muscle activity was observed in a velocity-changed condition in the weighted bat warm-up, as compared to a standard bat warm-up. It is suggested that weighted bat warm-up decreases the adjustment ability associated with inhibition of muscle activation under movement correction conditions.